Virtual reality for training emergency medicine residents in emergency scenarios: usefulness of a tutorial to enhance the simulation experience - Vittadello, A.; Savino, S.; Bressan, S.; Costa, M.; Boscolo, A.; Sella, N.; Pettenuzzo, T.; Zarantonello, F.; De Cassai, A.; Chang, T.; Navalesi, P.; Mormando, G. (Frontiers in Digital Health, 2025)
IntroductionCritical events in healthcare require a rapid and coordinated approach: simulation has been demonstrated a valid technique for training in emergency. Virtual Reality (VR) is an innovative technology that has revolutionized simulation training and healthcare professional development. A key phase of a simulation session with manikin consists in a familiarization with setting and equipment. The primary objective of this study is to investigate whether familiarization with a VR tutorial can change the perception of cases.MethodsEmergency medicine residents were randomly assigned to the Intervention group (n = 21) who undergone familiarization tutorial prior to the clinical scenario to a Control group (n = 21) where no familiarization tutorial was provided before the clinical scenario.ResultsNo significant differences were found between the two groups regarding perceived ease of use, but the Intervention group found VR familiarization useful and the Control group found it necessary to implement a VR tutorial. VR training was generally perceived by learners as a useful technology for training as confirmed by the literature.DiscussionFamiliarization seems to be an important phase of simulation-based training for trainees, even when running a VR-based simulation for an emergency scenario; it should be incorporated into the clinical VR sessions for simulation in healthcare settings.